2021
DOI: 10.1039/d0mh01826k
|View full text |Cite
|
Sign up to set email alerts
|

Nanotherapeutics using all-natural materials. Effective treatment of wound biofilm infections using crosslinked nanoemulsions

Abstract: Bacterial wound infections are a threat to public health. Although antibiotics currently provide front-line treatments for bacterial infections, the development of drug resistance coupled with the defenses provided through biofilm...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…In this study, oxanorbornene-based PNPs mimic antimicrobial peptides, but synthetic approaches enable fabrication of small size of nanoparticles, exhibiting multivalent interactions with the bacteria, as well as traverse the biofilm EPS matrix. Nanoparticles access a variety of antibacterial mechanisms, making the barrier to resistance development higher than for small molecule antibiotics that target specific processes [ 14 , 15 , 16 ]. The antimicrobial PONI-based polymers employed in this work are functionalized synthetic polymers that consist of cationic trimethylamine (TMA) head groups bridged to the PONI backbone by hydrophobic alkyl chains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, oxanorbornene-based PNPs mimic antimicrobial peptides, but synthetic approaches enable fabrication of small size of nanoparticles, exhibiting multivalent interactions with the bacteria, as well as traverse the biofilm EPS matrix. Nanoparticles access a variety of antibacterial mechanisms, making the barrier to resistance development higher than for small molecule antibiotics that target specific processes [ 14 , 15 , 16 ]. The antimicrobial PONI-based polymers employed in this work are functionalized synthetic polymers that consist of cationic trimethylamine (TMA) head groups bridged to the PONI backbone by hydrophobic alkyl chains.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is an urgent need for new treatment regimens to address multispecies biofilm infections. Recent advances in nanomaterial-based therapeutics provide a promising opportunity to effectively address difficult-to-treat bacterial and biofilm infections [14][15][16][17]. Polymeric nanoparticles provide versatile additions to the antimicrobial arsenal [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a murine wound biofilm model, it was found that nanoemulsions could reduce bacterial loads in wounds and accelerate wound healing. In a recent study, Li et al [183] . reported on a bacterial biofilm in vivo treatment that accelerated wound healing through the use of all‐natural materials.…”
Section: Wound Biofilm Therapymentioning
confidence: 99%
“…In ar ecent study,L ie tal. [183] reported on ab acterial biofilm in vivo treatment that accelerated wound healing through the use of all-natural materials.G elatin was stabilized by photo-crosslinking with riboflavin (vitamin B2) and carvacrol (the primary component in oregano oil) as the active antimicrobial component (Figure 19 a). Thee ngineered nanoemulsions were demonstrated to have broad-spectrum antimicrobial activity against…”
Section: Nanoemulsionsmentioning
confidence: 99%